The Influence of Audit Findings, Intergovernmental Transfers, and Leverage on Government Financial Performance - Laura, Prisca; Rita Martini; Okky Savira (LP2M IAIN Palopo, 2025)
This study was conducted to examine the influence of audit findings, intergovernmental transfers, and leverage on the financial performance of regency/municipal governments in South Sumatra Province, which is classified as very low based on the percentage of financial independence. The research employed a quantitative approach using secondary data obtained from the official website www.bpk.go.id. The population included 17 regencies/municipalities in South Sumatra Province, with a sample consisting of 349 observation units. The sample was selected using a saturated sampling technique. Hypothesis testing was carried out using multiple linear regression analysis and Eviews 12 software. The results of this study demonstrate that, partially, audit findings and leverage have no effect and are not significant on the financial performance of local governments in South Sumatra Province. Conversely, intergovernmental transfers significantly affect the financial performance of regency and municipal governments in South Sumatra Province. Simultaneous testing shows that the variables of audit findings, intergovernmental transfers, and leverage together have a significant effect on the financial performance of regency and municipal governments in South Sumatra Province.